Mántidos (Insecta: Mantodea) de la Reserva de la Biósfera Selva El Ocote, Chiapas, México - Hernández-Baltazar, Erick; Gómez, Benigno; Rodríguez-López, Misraim Edivaldo (Instituto de Ecología, A.C., 2019)
The objective of this work was to analyze the diversity of mantids in four localities of the Selva El Ocote Biosphere Reserve: a) Emilio Rabasa, b) Veinte Casas, c) Nuevo San Juan Chamula, and d) San Joaquín El Progreso, grouping them in sites of conservation (a, b) and disturbed sites (c, d). Eight field trips of five days each one were made, divided into the seasons with and without rain precipitation, from February to August 2016. The fieldwork of mantids was done using light traps (black and white), in addition to direct manual capture. In total, 38 individuals were captured, five genera and seven species within three families. In addition, four new records of these insects were made for Chiapas (17 in total), which represents 23.6% of the known mantids in the country. The conservation sites presented high diversity, while the localities with more shared species were Veinte Casas and Nuevo San Juan Chamula. In April and July more mantids were collected compared to the other dates. The contribution of ecological-taxonomic data in this study is of importance to enrich the knowledge of this group of insects.